TolF locus in Escherichia coli: chromosomal location and relationship to loci cmlB and tolD. - Foulds, J (1976)
The tentative map position on the Escherichia coli chromosome of the tolF locus, determining tolerance to colicins A, E2, E3, K, and L, has been confirmed by three-point transduction. It lies between the aroA and pyrD loci at about 21 min on the linkage map of Bachmann et al. (1976). The cmlB locus, determining increased resistance to the antibiotics chloramphenicol and tetracycline, also lies in this region (Reeve, 1966). Phenotypic and genetic comparison of isogenic strains that carry a mutation in either the tolF or cmlB locus makes it likely that these loci are closely related or identical. The tolD locus determining tolerance to colicins E2 and E3 as well as increased resistance to antibiotics has been reported to be located close to the aroA locus as a result of conjugation experiments (Eriksson-Grennberg et al. 1965). However, tolD did not cotransduce with any of several loci in this region, indicating that the mutation is not located within the region of the genetic map corresponding to approximately 19 to 22.5 min.